039: BIRTH PREPAREDNESS, COMPLICATION READINESS AND ASSOCIATED FACTORS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINICS AT MEDICAL OFFICER OF HEALTH (MOH) AREA PADUKKA. (24th August 2015) - Rodrigo, Chithramali H; Kumarapeli, Vindya
Abstract : Background: Obstetric emergencies need prior preparation. 'Birth Preparedness and Complication Readiness' (BPCR) is a concept that promotes timely maternal care. Objectives: This study assessed BPCR and associated factors among pregnant women attending antenatal clinics (ANCs) in MOH area Padukka. Methods: A descriptive cross-sectional study was carried out in 2014, among a random sample of 280 third trimester pregnant women, attending ANCs in MOH area Padukka. Data were collected using a pre-tested interviewer administered questionnaire. Satisfactory BPCR was if accomplished ≥6 components of 8; desired place of birth, closest care facility, birth-related expenses, emergency expenses, person to accompany, arrangements to look after other children, transport for birth, transport in an obstetric emergency. Result: Response rate was 95.9% (n=269). Median age was 29 years (IQR; 25–32). Pregnancy was planned by 84.0% (n=226), 81.0% (n=218) had registered with PHM ≤8 weeks, 58.4% (n=157) had attended ≥5 ANCs, 10.8% (n=29) had attended all ante-natal classes, 75.8% (n=204) had discussed BPCR plan with healthcare provider. Only 60.2% (n=162) had satisfactory knowledge on pregnancy, delivery and post-partum danger signs, 75.0% (n=207) had favourable attitudes towards BPCR, 68.6% (n=185) had favourable perceptions on BPCR services. Of them 86.2% (n=232) had satisfactory BPCR which was significantly associated with planned pregnancy, registration ≤8 weeks, ≥5 ANCs, ≥1 antenatal classes, discussing BPCR plan with healthcare provider, knowledge on pregnancy and post-partum danger signs, favourable attitudes and favourable perceptions (p<0.05). Conclusion: Knowledge on danger signs and attitudes towards BPCR need improvement. Sustainable, culturally sensitive BPCR practice models are needed.